The Notion of Arete in Proclus'Commentary to Plato's First Alcibiades - Moutsopoulos, Evanghélos (1999)
In this paper the A. discusses Proclus' determinations of Plato's conception of arete, successively dealing with virtue 's nature, its teaching and its axiology. Both for Plato as for Proclus. "virtue" is an innate quality that should be manifest through our acts, in order of which its teaching would be a process of assisted self-revelation. In view of the thesis of logical-practical parallelism (akin to the Aristotelian logical-grammatical parallelism). Proclus concludes that the reexists an inner harmony of the soul determined by the inner harmony of each of its three parts. Thus justiceis seen as the virtue of the whole soul. and virtue rises then as the criterion of good, beauty, and of any value in general.